Correlation analysis of serum IL1RL1, DAPPER5, and MFGF with poor prognosis in patients with heart failure: Serum IL1RL1, DAPPER5, and MFGF in prognosis of heart failure - Yu, Cheng; Cao, Suyan; Zhang, Ying; Zhao, Yuyu; Dong, Menghao; Liu, Yulong (Journal of Medical Biochemistry, 2026)
Objective To explore the predictive value of the combined effect of serum Interleukin-1 Receptor-like 1 (IL1RL1), Dishevelled-associated protein 5 (DAPPER5), and Metabolic fibroblast growth factor (MFGF) on poor prognosis in patients with heart failure with preserved ejection fraction (HFpEF).Methods The study group consisted of 382 HFpEF patients who were diagnosed and treated at this facility between July 2023 and August 2025. The control group consisted of 382 additional healthy people who were examined physically in the same hospital over the same time period. Patients were monitored for a year following their release from therapy. The poor prognosis group comprised patients who had adverse cardiovascular events throughout the follow-up period, while the good prognosis group included the remaining patients. Each research participant's serum levels of IL1RL1, DAPPER5, and MFGF were assessed using an enzyme-linked immunosorbent assay. Using multivariate logistic analysis, the factors influencing the poor prognosis of HFpEF patients were investigated. A receiver operating characteristic (ROC) curve was developed to evaluate the predictive significance of serum IL1RL1, DAPPER5, and MFGF independently and in combination for a poor prognosis in patients with HFpEF.Results While the study group's serum DAPPER5 level was lower than the control group's, the study group's serum IL1RL1 and MFGF levels were higher. There was a statistically significant change (P
Keywords: Interleukin-1 Receptor-like 1; Dishevelled-associated protein 5; Metabolic fibroblast growth factor; Heart failure; Prognostic predictive value